2006
DOI: 10.1021/ja057832n
|View full text |Cite
|
Sign up to set email alerts
|

15N NMR Spin Relaxation Dispersion Study of the Molecular Crowding Effects on Protein Folding under Native Conditions

Abstract: The effects of macromolecular crowding on protein stability and folding kinetics have been studied using the recently developed 15N spin relaxation dispersion technique. By applying this method to a redesigned apocytochrome b562, the kinetics and thermodynamics of the protein folding processes in both the presence and the absence of crowding agents have been characterized. The result indicates that, even under the mild crowded environments (in the presence of 85 mg/mL of PEG 20K), the folding rate of the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 13 publications
(36 reference statements)
5
75
0
Order By: Relevance
“…In contrast to the significant stabilization effects seen for confinement, experimental studies on macromolecular crowding from different laboratories have consistently found a modest effect on protein stability [43][44][45][46][47][48]. The theoretical prediction of modest stabilizing effect by crowding, presented earlier, thus appears to have experimental support.…”
Section: Effect Of Macromolecular Crowding On Folding Stabilitymentioning
confidence: 77%
See 1 more Smart Citation
“…In contrast to the significant stabilization effects seen for confinement, experimental studies on macromolecular crowding from different laboratories have consistently found a modest effect on protein stability [43][44][45][46][47][48]. The theoretical prediction of modest stabilizing effect by crowding, presented earlier, thus appears to have experimental support.…”
Section: Effect Of Macromolecular Crowding On Folding Stabilitymentioning
confidence: 77%
“…[46] studied the effect of dextran 30 on the heat and cold denaturation of the molten globule form of apomyoglobin; a stabilization effect of ~0.5k B T was observed at 270 g/l of the crowding agent. Based on NMR relaxation dispersion data obtained under native conditions, Ai et al [47] found that the folding stability of a redesigned four helix-bundle protein is increased bỹ 04k B T in the presence of 85 g/l PEG 20000. Ignatova et al [48] even reported preliminary data indicating a small destabilizing effect by Ficoll 70 on cellular retinoic acid-binding protein I.…”
Section: Effect Of Macromolecular Crowding On Folding Stabilitymentioning
confidence: 99%
“…Earlier experimental work has focused on the effects of crowding on kinetic refolding of complex proteins and on protein nonnative states at extreme conditions, whereas theoretical approaches have instead involved simple lattice models or small peptide systems (1,(9)(10)(11)(12)). …”
Section: Discussionmentioning
confidence: 99%
“…Experimental and theoretical work has demonstrated large effects of crowding on the thermodynamics and kinetics of many biological processes, including protein binding, folding, and aggregation (1,(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Slower folding is consistent with the viscosity increase. Slower unfolding in Ficoll is consistent with both viscosity and an entropic pressure for protein compaction (25,26); however, limiting the explanation to viscosity and compaction effects is probably too simple. In contrast, BSA had only small effects, whereas lysozyme slowed folding fivefold but had no effect on unfolding.…”
Section: Folding and Unfolding Rates Confirm Preferential Interactionmentioning
confidence: 92%